Model Bimbingan Dan Konseling Komprehensif Dalam Layanan Perencanaan Karir Siswa Smk - Yunita Dwi Aryani; Akhmad Fajar Prasetya; Dody Hartanto; Agus Ria Kumara (CV. SINAR HOWUHOWU, 2025)
This study aims to describe the implementation of the Comprehensive Guidance and Counseling (GC) Model in career planning services for vocational high school (SMK) students. The research background is based on the challenges of transitioning from school to the workforce, which requires students’ career readiness, including the development of competencies, career knowledge, and adaptability to industrial dynamics. This study employs a mixed-method approach, collecting data through questionnaires, interviews, observations, and document analysis. Participants include SMK students, guidance counselors, and related stakeholders. Data analysis is conducted using descriptive qualitative and quantitative methods to provide a holistic view of the effectiveness of comprehensive GC services. The findings indicate that GC services integrating assessment, individual counseling, group guidance, and career information enhance students’ career readiness. Assessment of students’ interests, talents, and competencies serves as the foundation for personalized and relevant career planning. Continuous evaluation and monitoring provide feedback for service improvement, enabling students to develop career adaptability, self-efficacy, and positive attitudes in career decision-making. This study highlights that comprehensive GC is an effective strategy to prepare students for workforce challenges.